TINDAK PIDANA PENGANIAYAAN DENGAN SENGAJA MENYEBABKAN CEDERA BERAT (PUTUSAN NOMOR 561/PID.B/2021/PN.SBY): The Crime Of Torture With Intentional Cause Serious Injury (Desicion Number 561/Pid.B/2021/PN.Sby) - Syach Zaky Sultan; Maria Silvya Elisabeth Wangga (AMICUS CURIAE, 2025)
The crime of assault perpetrated by the perpetrator against the victim has involved violent behavior that can cause various types of physical injuries to the victim. However, the victim may also experience serious psychological impacts due to the violence they have endured. The identification issues raised are: what are the criteria for intentional assault causing serious injury in Decision Number 561/Pid.B/2021/PN. Sby, and does the perpetrator's action of intentionally causing serious injury meet the qualifications of Article 351 Paragraph (2) in Decision Number 561/Pid.B/2021/PN.Sby. This research employs a normative research method with descriptive-analytical characteristics, utilizing both primary and secondary data obtained through literature review and analyzed qualitatively using deductive logical conclusion drawing. The research findings conclude that the defendant's actions have caused severe injuries to the victim by the criteria of Article 90 of the Indonesian Criminal Code (KUHP), which involves conditions of illness or injuries that do not provide hope for recovery or even result in death and there is appropriateness of the punishment and criminal sanctions given in this case. In the researcher's view, the charges that should have been brought forth are based on Article 351 Paragraph (2) of the Indonesian Criminal Code (KUHP) because the injuries suffered by the victim fall into the category of severe assault.